Implementation of Evidence-Based Presurgical Testing Guidelines in Patients Undergoing Ambulatory Surgery for Endometrial Cancer. Issue 1 (January 2022) - Aviki, Emeline M.; Gordhandas, Sushmita B.; Velzen, Jeena; Riley, Michael; Manning-Geist, Beryl; Rice, Jonathan; Weiss, Hallie; Abu-Rustum, Nadeem R.; Gardner, Ginger J.
Abstract : PURPOSE: The aim of this quality improvement intervention was to evaluate the safety and cost savings of presurgical testing (PST) guidelines for patients undergoing hysterectomy for endometrial pathology in the ambulatory setting. METHODS: Evidence-based presurgical testing (PST) guidelines were developed by a multidisciplinary team. These guidelines were implemented on the gynecologic surgery service of a comprehensive cancer center in January 2016. All patients with a diagnosis of endometrial pathology who underwent ambulatory surgery during the specified time periods were included in this analysis. A pre-post analysis was performed (preperiod, July 2014-December 2015; postperiod, July 2016-December 2017). Rates of completed presurgical tests and perioperative adverse events were compared between time periods. Cost savings related to the reduction in PST were calculated using the direct cost of testing and reported in percentage cost reduction. RESULTS: A total of 749 hysterectomies were completed in the preperiod and 775 in the postperiod. After implementation of PST guidelines, complete blood counts, coagulation testing, comprehensive metabolic panels, chest x-rays, and electrocardiograms were reduced by 13.4%, 78.1%, 36.8%, 39.0%, and 15.5%, respectively (all P < .001). Rates of perioperative cardiopulmonary adverse events (0% v 0%) and hematologic adverse events (3.3% v 2.0%; P = .10) were stable between time periods. There were no deaths within 90 days of surgery. There was a 41.4% reduction in direct costs related to PST in the postperiod. CONCLUSION: The use of evidence-based PST guidelines for patients with endometrial pathology undergoing hysterectomy in the ambulatory setting is safe and cost-effective. A multidisciplinary approach is essential for successful development and implementation.